TAJWID ANIMATED LEARNING EASY METHOD OF READING AL-QUR'AN using Macromedia Flash MX 8ACT - Winata Triana; Hariyanto Hariyanto (Jurnal Sistem Informasi, 2009)
Abstract :In studying the Qur'an's most basic is to learn reading the Qur'an, learn about punctuation, reading and understanding the law. To learn more about reading the Qur'an in a good and perfect the science needed tajwid. Tajwid Science in the Qur'an is very important as it relates directly with the Qur'an. Even in a world of science of hadith, a hadith alim not going to teach his students that he had knowledge of the Qur'an. "The best of you is studying the Quran and teach it" (Narrated by Bukhari). Therefore, the authors create a writing titled Animation Learning Easy Reading the Qur'an, which in scientific writing is made by using Macromedia Flash 8 MX object-oriented in order to be able to utilize existing facilities within the object.Bibliography: 5, (1994 to 2009)